A polyurethane-based graphene high-thermal-conductivity composite film and a preparation method thereof

CN122978684APending Publication Date: 2026-10-27INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147745.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有技术中,制备聚氨酯/石墨烯高导热复合膜主要分为三类主流技术路线:第一类为直接填充共混与石墨烯膜分层压合方案,直接将石墨烯粉体简单混入聚氨酯、硅橡胶、环氧树脂等高分子基体,依靠提升石墨烯填充量搭建导热通路;或将独立石墨烯导热膜与聚氨酯基底物理辊压粘合,形成分层复合膜结构;第二类为石墨烯预改性方案,采用传统Hummers氧化法,借助浓硫酸、高锰酸钾等强氧化试剂对石墨烯表面氧化接枝含氧基团,改善石墨烯与高分子基体的分散相容性;第三类为特殊定向工艺方案,依托3D打印、双向冷冻、气相沉积、激光诱导取向等特殊设备调控石墨烯片层定向排布,构建贯通型导热网络;上述三类方案虽可在一定程度上提升复合膜导热性能,但均存在难以兼顾的多重固有缺陷,制约其工业化批量应用,具体问题如下:

Benefits of technology

[0037](1)针对传统强氧化改性工艺存在的污染大、破坏石墨烯本征结构的问题,本发明采用温和有机异氰酸酯共价改性路径,无需使用浓硫酸、高锰酸钾等强氧化剂,无大量有毒含酸废水排放,工艺绿色环保;同时完整保留了石墨烯的高结晶片层结构,避免了改性过程产生的结构缺陷引发的声子散射,充分发挥了石墨烯的本征高导热特性,解决了传统改性工艺降本降性能的矛盾;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978684A_ABST
    Figure CN122978684A_ABST
Patent Text Reader

Abstract

The application discloses a polyurethane-based graphene high-thermal-conductivity composite film and a preparation method thereof, relates to the technical field of graphene composite films, and comprises the following raw materials: isocyanate-based polyurethane prepolymer, modified graphene, hydroxyl-modified carbon quantum dots, hydroxylated single-walled carbon nanotubes, a dispersing agent, a film-forming agent and N,N-dimethylformamide. The application realizes performance balance and mass production adaptation through multi-scale filler cooperation and process adaptation, constructs a three-dimensional continuous heat conduction network by relying on two-dimensional graphene, one-dimensional carbon nanotubes and zero-dimensional carbon quantum dots, the two-dimensional graphene provides a main heat conduction carrier, the one-dimensional carbon nanotubes bridge the gaps between the graphene, and the zero-dimensional carbon quantum dots fill micro-nano defects, so that the interface thermal resistance is greatly reduced and the vertical direction thermal conductivity is improved; meanwhile, the chemical bond between the graphene and the polyurethane is realized through in-situ covalent grafting, the interface thermal resistance caused by physical adhesion is eliminated, mature casting coating processes are adopted throughout the whole process, special customized equipment is not needed, and the existing production line can be directly adapted for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of graphene composite film technology, specifically to a polyurethane-based graphene high thermal conductivity composite film and its preparation method. Background Technology

[0002] With the rapid iteration of consumer electronics, wearable flexible devices, new energy power batteries, and high-density chip packaging, the integration of devices continues to increase and the heat generation power per unit volume increases significantly. This has led to an increasingly urgent demand for thermal interface thin film materials that combine high thermal conductivity, high flexibility, excellent mechanical durability, and scalable processing capabilities. Polyurethane (PU) elastomers possess advantages such as lightweight, high elasticity, bending resistance, good adhesion, and easy film formation, making them ideal matrix materials for flexible thermally conductive films. Graphene, with its ultra-high intrinsic thermal conductivity and ultra-thin two-dimensional sheet structure, is widely recognized as one of the best polymer thermally conductive fillers. Therefore, polyurethane-based graphene composite thermally conductive films have become a research hotspot in the field of flexible thermal management materials.

[0003] In existing technologies, the preparation of polyurethane / graphene high thermal conductivity composite films mainly falls into three mainstream technical routes: The first is a direct filling blending and graphene film layering and lamination scheme, which directly mixes graphene powder into polymer matrices such as polyurethane, silicone rubber, and epoxy resin, relying on increasing the graphene filling amount to build thermal conductivity pathways; or physically roll-pressing and bonding independent graphene thermal conductive films with polyurethane substrates to form a layered composite film structure; the second is a graphene pre-modification scheme, which uses the traditional Hummers oxidation method, employing strong oxidizing reagents such as concentrated sulfuric acid and potassium permanganate to oxidize and graft oxygen-containing groups onto the graphene surface, improving the dispersion compatibility between graphene and the polymer matrix; the third is a special orientation process scheme, which relies on special equipment such as 3D printing, bidirectional freezing, vapor deposition, and laser-induced orientation to control the directional arrangement of graphene sheets and construct a through-type thermal conductive network. Although the above three schemes can improve the thermal conductivity of composite films to a certain extent, they all have multiple inherent defects that are difficult to balance, restricting their industrial mass application. The specific problems are as follows:

[0004] In direct filling schemes, graphene is prone to agglomeration in polymers due to its high surface energy, making it impossible to form continuous thermal conductivity pathways. Increasing the filling amount to improve thermal conductivity will damage the molecular structure of the polymer, significantly reducing the mechanical and adhesive properties of the composite film. In simple layered structures, graphene and polymers are only bonded by physical interactions, resulting in poor interfacial bonding and easy delamination, which introduces additional interfacial thermal resistance. At the same time, the longitudinal thermal conduction path is discontinuous, and the thermal resistance in the thickness direction is relatively high. Conventional graphene modification processes rely on strong oxidizing and toxic reagents such as concentrated sulfuric acid and potassium permanganate, which are not only demanding and costly, but also prone to environmental pollution. They may even damage the intrinsic structure of graphene, introducing phonon scattering defects and reducing its intrinsic thermal conductivity. Special preparation processes have high equipment requirements, complex process parameter control, and high production costs, making it difficult to achieve large-scale mass production and hindering industrial applications.

[0005] Furthermore, existing technologies mostly use graphene as a single thermally conductive filler, relying solely on two-dimensional sheets to build thermally conductive channels. There are a large number of micron-level gaps between the sheets, lacking filler bridging and defect filling mechanisms, making it difficult to further reduce interfacial thermal resistance. If carbon nanotubes or carbon quantum dots are used as auxiliary fillers, multi-scale filler synergy matching is not achieved, making it impossible to form a three-dimensional continuous thermally conductive network with "two-dimensional main heat carrier, one-dimensional bridging gaps, and zero-dimensional filling of micro-defects". The improvement in vertical thermal conductivity is limited with low filler content, and high filler content is still required to achieve the target thermal conductivity, failing to balance the three core properties of thermal conductivity, flexibility, and mechanical durability.

[0006] In summary, current polyurethane-based graphene thermally conductive composite film technology suffers from multiple drawbacks, including easy graphene agglomeration, deterioration of flexible mechanical properties due to high filler content, significant pollution and damage to the thermally conductive structure of graphene by traditional modification processes, high thermal resistance and easy peeling at the layered composite interface, difficulty in mass production with advanced molding processes, and incomplete thermal conductivity pathways due to single-component fillers. There is an urgent need to develop a green and mildly modified polyurethane-based graphene high thermal conductivity composite film and its preparation method that features low filler addition, chemical bonding between filler and matrix, synergistic construction of a three-dimensional thermally conductive network by multi-scale carbon fillers, and compatibility with mature casting coating production lines. Summary of the Invention

[0007] To address the aforementioned issues, this invention provides a polyurethane-based graphene high thermal conductivity composite film and its preparation method. This invention achieves performance balance and mass production suitability through multi-scale filler synergy and process adaptation. It utilizes a three-dimensional continuous thermally conductive network constructed from two-dimensional graphene, one-dimensional carbon nanotubes, and zero-dimensional carbon quantum dots. Two-dimensional graphene provides the primary heat transfer medium, one-dimensional carbon nanotubes bridge the gaps between graphene particles, and zero-dimensional carbon quantum dots fill micro-nano defects, significantly reducing interfacial thermal resistance and improving vertical thermal conductivity. Simultaneously, in-situ covalent grafting achieves chemical bonding between graphene and polyurethane, eliminating interfacial thermal resistance caused by physical adhesion. The entire process employs a mature casting coating process, requiring no special customized equipment and directly adapting to existing production lines for large-scale production. This solves the pain point of special processes being difficult to industrialize, achieving a balance between thermal conductivity, mechanical properties, and production costs.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] A polyurethane-based graphene high thermal conductivity composite film comprises the following raw materials in parts by weight: 76-93.9 parts of polyurethane prepolymer, 5-20 parts of modified graphene, 1-3 parts of hydroxyl-modified carbon quantum dots, 0.3-0.8 parts of hydroxylated single-walled carbon nanotubes, 0.1-0.3 parts of dispersant, 0.1-1 parts of film-forming agent, and 150-300 parts of N,N-dimethylformamide.

[0010] This invention addresses the pain points of existing technologies by designing a multi-dimensional synergistic formulation system. This formulation achieves high thermal conductivity while maintaining the original flexible mechanical properties of the polyurethane matrix, thus avoiding performance degradation caused by high filler content.

[0011] Preferably, the modified graphene is prepared by dispersing graphene oxide in a solvent to obtain a graphene oxide dispersion, then adding an organic isocyanate to the graphene oxide dispersion, and stirring the mixture under nitrogen protection for 12-24 hours to complete the modification, thereby obtaining a modified graphene dispersion.

[0012] This invention utilizes interface modification technology, abandoning the traditional strong oxidation modification route of concentrated sulfuric acid, and adopts mild covalent modification with organic isocyanate. This not only solves the problem of graphene dispersion and compatibility in polyurethane, but also avoids the damage to the intact graphene sheets caused by strong oxidation, thus preserving the intrinsic high thermal conductivity of graphene to the greatest extent. At the same time, the entire process is green and environmentally friendly, with no toxic acid wastewater discharge, and the process conditions are milder and the cost is lower.

[0013] Preferably, the concentration of the graphene oxide dispersion is 1-100 mg / ml;

[0014] The concentration of the organic isocyanate in the graphene oxide dispersion is 0.1-10 mmol / L; the organic isocyanate includes any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexylmethylene diisocyanate, phenyldimethyl diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and dimer diisocyanate.

[0015] The stirring speed is 1000-2000 rpm;

[0016] The reaction temperature is 70-80℃;

[0017] The solvent is N,N-dimethylformamide.

[0018] Preferably, the method for preparing the hydroxyl-modified carbon quantum dots is as follows: using glucose as a carbon source, the carbon is hydrothermally carbonized to obtain carbon quantum dots with a surface rich in hydroxyl groups;

[0019] The method for preparing the hydroxylated single-walled carbon nanotubes is as follows: single-walled carbon nanotubes are placed in an aqueous sodium hydroxide solution for hydrothermal oxidation, and hydroxyl groups are introduced into the tube wall to obtain hydroxylated single-walled carbon nanotubes.

[0020] Preferably, the hydrothermal carbonization temperature is 170°C.

[0021] Preferably, the method for preparing the isocyanate-terminated polyurethane prepolymer is as follows: under nitrogen protection, polyisocyanate and polyol are reacted at 75-80℃ for 1-3 hours, and after cooling to 60℃, chain extender, hydrophilic agent and catalyst are added, and the reaction is continued at 60-80℃ for 3-6 hours to obtain the isocyanate-terminated polyurethane prepolymer.

[0022] Preferably, the molar mass ratio of the organic isocyanate, polyol, chain extender, hydrophilic agent and catalyst is 2 mol: 1 mol: 0.7 mol: 0.3 mol: 0.02 g.

[0023] Preferably, the organic isocyanate includes any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexylmethylene diisocyanate, phenyldimethyl diisocyanate, 2,2,4-trimethylhexane diisocyanate, and dimer diisocyanate.

[0024] The polyol includes any one of polybutylene glycol 1000, polybutylene glycol 2000, and polybutylene glycol 3000;

[0025] The chain extender is 1,4-butanediol;

[0026] The hydrophilic agent includes any one of 2,2-dihydroxymethylbutyric acid and 1,4-bis(2-hydroxyethoxy)benzene;

[0027] The catalyst is dibutyltin dilaurate.

[0028] Preferably, the raw materials include the following parts by weight: 80-90 parts of isocyanate-terminated polyurethane prepolymer, 5-10 parts of modified graphene, 1-2 parts of carbon quantum dots, 0.5 parts of carbon nanotubes, 0.1-0.3 parts of dispersant, 0.1-1 parts of film-forming agent, and 150-300 parts of N,N-dimethylformamide.

[0029] Preferably, the dispersant is a polyacrylate dispersant;

[0030] The film-forming agent is an acrylic film-forming agent.

[0031] The preparation method of the polyurethane-based graphene high thermal conductivity composite film described above specifically includes the following steps:

[0032] (1) The modified graphene dispersion was added to the polyurethane prepolymer with terminal isocyanate group and reacted for 1-2 hours under the action of the catalyst dibutyltin dilaurate to achieve in-situ covalent grafting. After neutralization and emulsification, the solvent was recovered by vacuum distillation to obtain polyurethane composite emulsion.

[0033] (2) Carbon quantum dots, carbon nanotubes, dispersant, film-forming agent and N,N-dimethylformamide are added to the polyurethane composite emulsion and mixed evenly. The film is formed by casting or doctor blade coating process and dried to obtain a polyurethane-based graphene high thermal conductivity composite film.

[0034] Preferably, the specific steps of neutralization and emulsification in step (1) are as follows: triethylamine is slowly added dropwise to neutralize to pH = 6.5-7.5;

[0035] The reaction temperature described in step (1) is 60-65℃.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) In view of the problems of high pollution and destruction of the intrinsic structure of graphene in traditional strong oxidation modification process, the present invention adopts a mild organic isocyanate covalent modification path, which does not require the use of strong oxidants such as concentrated sulfuric acid and potassium permanganate, and does not discharge a large amount of toxic acid wastewater, making the process green and environmentally friendly; at the same time, the highly crystalline sheet structure of graphene is completely preserved, avoiding phonon scattering caused by structural defects generated during the modification process, giving full play to the intrinsic high thermal conductivity of graphene, and solving the contradiction of cost reduction and performance reduction in traditional modification process;

[0038] (2) In view of the problems of graphene agglomeration and poor interfacial compatibility in direct physical blending, the present invention uses an in-situ grafting composite process to form covalent bonds between the surface active groups of modified graphene and the end groups of polyurethane prepolymer, rather than simple physical mixing. This not only achieves uniform dispersion of graphene in polyurethane matrix with low filling amount, but also completely eliminates the interfacial thermal resistance between filler and matrix. Compared with physical composite process, the vertical thermal conductivity can be increased by more than 20% under the same filling amount.

[0039] (3) In response to the industry pain point of deteriorated mechanical properties due to high filling, this invention constructs a three-dimensional continuous thermal conductive network by synergistic multi-scale fillers of two-dimensional graphene, one-dimensional carbon nanotubes and zero-dimensional carbon quantum dots. Only 5-10wt% of low graphene addition is required to achieve high thermal conductivity. Compared with the traditional direct filling scheme, the filler dosage is reduced by more than 40% when the same thermal conductivity is achieved. The molecular chain flexibility of the polyurethane matrix is ​​fully preserved. The tensile strength, bonding strength and compression resilience of the composite film are all improved by more than 15%, realizing the synergistic optimization of thermal conductivity and mechanical properties.

[0040] (4) In terms of process adaptability, the present invention adopts mature casting and coating processes throughout the process, without the need for special customized equipment such as 3D printing and vapor deposition. The process parameters are easy to control and the production cost is low. It can be directly based on existing production lines to achieve large-scale and stable production, which solves the problem that most new thermal conductive composite film technologies have excellent performance but are difficult to industrialize. It is suitable for batch supply needs of multiple application scenarios such as thermal management of electronic components, wearable electric heating devices, and thermal control of new energy batteries. Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings in this description are merely embodiments of the present invention.

[0042] Figure 1 This is a bar chart showing the thermal conductivity and bending performance of the product in Embodiment 1 of the present invention;

[0043] Figure 2 This is a graph showing the thermal conductivity results of the product in Embodiment 1 of the present invention after 10,000 continuous bending cycles;

[0044] Figure 3 The above are bar charts showing the thermal conductivity of the products in Embodiments 2 and 3 of this invention.

[0045] Figure 4 This is a tensile stress-strain curve of the product in Embodiment 2 of the present invention;

[0046] Figure 5 This is a graph showing the rate of dimensional change of the product in Example 2 of the present invention after being placed at 100°C for 10 days.

[0047] Figure 6 The diagram shows the junction temperature curves of the product in Embodiment 3 of this invention and the traditional polyimide-based aluminum foil heat dissipation backsheet chip.

[0048] Figure 7 This is a stress-strain curve of the adhesive bonding of the product in Embodiment 3 of the present invention. Detailed Implementation

[0049] Embodiments of the present invention are described below, examples of which are shown in the accompanying drawings. The embodiments described with reference to the drawings are exemplary and intended to explain the present invention, but are not to be construed as limiting the present invention.

[0050] Example 1

[0051] This invention provides a method for preparing a polyurethane-based graphene high thermal conductivity composite film, specifically including the following steps:

[0052] (1) Weigh the raw materials according to the following weight parts: 85 parts of isocyanate-terminated polyurethane prepolymer, 6 parts of hydroxyl-modified graphene, 1.2 parts of hydroxyl-modified carbon quantum dots, 0.5 parts of hydroxylated single-walled carbon nanotubes, 0.2 parts of polyacrylate dispersant, 0.4 parts of acrylic film-forming agent, and 200 parts of DMF solvent.

[0053] The preparation method of the isocyanate-terminated polyurethane prepolymer is as follows: under nitrogen protection, hexamethylene diisocyanate and polybutanediol 1000 are reacted at 75°C for 2 hours. After cooling, 1,4-butanediol, 2,2-dimethylolbutyric acid and dibutyltin dilaurate are added, and the reaction is continued at 60°C for 3 hours to obtain the isocyanate-terminated polyurethane prepolymer. The molar ratio of hexamethylene diisocyanate, polybutanediol 1000, 1,4-butanediol, 2,2-dimethylolbutyric acid and dibutyltin dilaurate is 2 mol:1 mol:0.7 mol:0.3 mol:0.02 g.

[0054] The modified graphene was prepared as follows: graphene oxide was dispersed in N,N-dimethylformamide to obtain a graphene oxide dispersion with a concentration of 50 mg / ml. Then, hexamethylene diisocyanate with a concentration of 5 mmol / L was added to the graphene oxide dispersion. The modification was completed by stirring at 80°C and 1500 rpm for 18 h under nitrogen protection to obtain the modified graphene dispersion.

[0055] The preparation method of hydroxyl-modified carbon quantum dots is as follows: using glucose as a carbon source, carbonization is carried out at 170℃ to directly prepare carbon quantum dots with hydroxyl-rich surfaces;

[0056] The preparation method of hydroxylated single-walled carbon nanotubes is as follows: single-walled carbon nanotubes are placed in a 3 mol / L sodium hydroxide aqueous solution and hydrothermally oxidized at 180℃ for 6 h to introduce hydroxyl groups into the tube wall to obtain hydroxylated single-walled carbon nanotubes.

[0057] (2) The modified graphene dispersion was added to the polyurethane prepolymer with terminal isocyanate group and reacted at 60°C for 2 hours under the action of the catalyst dibutyltin dilaurate to achieve in-situ covalent grafting. Triethylamine was slowly added dropwise to neutralize to pH=6.5-7.5 and then the solvent was recovered by vacuum distillation to obtain polyurethane composite emulsion.

[0058] (3) Hydroxyl-modified carbon quantum dots, hydroxylated single-walled carbon nanotubes, polyacrylate dispersant (manufacturer: Wanhua Chemical; model: K45), acrylic film-forming agent (manufacturer: Shengxingxing LOCA; model: LOCA A+) and DMF solvent were added to the polyurethane composite emulsion and mixed evenly. The film was formed by doctor blade coating process with a doctor blade gap of 100 μm and dried at 100℃ for 2 h to obtain a polyurethane-based graphene high thermal conductivity composite film with a final film thickness of 50 μm.

[0059] The results of the test are as follows: Figure 1-2 The composite film prepared in this embodiment has a room temperature vertical thermal conductivity of 12.5 W / (m·K), a tensile strength of 32 MPa, an elongation at break of 480%, and a thermal conductivity retention rate of over 97% after 10,000 consecutive bending cycles. It is suitable for the thermal management requirements of wearable electronic flexible devices and has a 27% improvement in thermal conductivity compared to physical blending schemes with the same filler content.

[0060] Example 2

[0061] This invention provides a method for preparing a polyurethane-based graphene high thermal conductivity composite film, specifically including the following steps:

[0062] (1) Weigh the raw materials according to the following weight parts: 82 parts of isocyanate-terminated polyurethane prepolymer, 9 parts of hydroxyl-modified graphene, 1.8 parts of hydroxyl-modified carbon quantum dots, 0.7 parts of hydroxylated multi-walled carbon nanotubes, 0.2 parts of polyacrylate dispersant, 0.8 parts of acrylic film-forming agent, and 220 parts of DMF solvent.

[0063] The preparation method of the isocyanate-terminated polyurethane prepolymer is as follows: Isophorone diisocyanate and polybutylene glycol 2000 are reacted at 75℃ for 2 hours under nitrogen protection. After cooling, 1,4-butanediol, 2,2-dimethylolbutyric acid, and dibutyltin dilaurate are added, and the reaction is continued at 60℃ for 3 hours to obtain the isocyanate-terminated polyurethane prepolymer. The molar ratio of isophorone diisocyanate, polybutylene glycol 2000, 1,4-butanediol, 2,2-dimethylolbutyric acid, and dibutyltin dilaurate is 2 mol:1 mol:0.7 mol:0.3 mol:0.02 g.

[0064] The modified graphene was prepared by dispersing graphene oxide in N,N-dimethylformamide to obtain a graphene oxide dispersion with a concentration of 50 mg / ml. Then, isophorone diisocyanate with a concentration of 5 mmol / L was added to the graphene oxide dispersion. The modification was completed by stirring at 75°C and 1800 rpm for 20 h under nitrogen protection.

[0065] The preparation method of hydroxyl-modified carbon quantum dots is as follows: using glucose as a carbon source, carbonization is carried out at 170℃ to directly prepare carbon quantum dots with hydroxyl-rich surfaces;

[0066] The preparation method of hydroxylated single-walled carbon nanotubes is as follows: single-walled carbon nanotubes are placed in a 3 mol / L sodium hydroxide aqueous solution and hydrothermally oxidized at 180℃ for 6 h to introduce hydroxyl groups into the tube wall to obtain hydroxylated single-walled carbon nanotubes.

[0067] (2) The modified graphene dispersion was added to the polyurethane prepolymer with terminal isocyanate group and reacted at 65°C for 1.5 h under the action of the catalyst dibutyltin dilaurate to achieve in-situ covalent grafting. Triethylamine was slowly added dropwise to neutralize to pH=6.5-7.5 and then the solvent was recovered by vacuum distillation to obtain polyurethane composite emulsion.

[0068] (3) Hydroxyl-modified carbon quantum dots, hydroxylated single-walled carbon nanotubes, polyacrylate dispersant (manufacturer: Wanhua Chemical; model: K45), acrylic film-forming agent (manufacturer: Shengxingxing LOCA; model: LOCA A+) and DMF solvent were added to the polyurethane composite emulsion and mixed evenly. The film was formed by doctor blade coating process with a doctor blade gap of 100 μm. After drying for 3 h in stages (80℃→110℃→120℃), a polyurethane-based graphene high thermal conductivity composite film was obtained with a final film thickness of 70 μm.

[0069] Through testing, the room temperature vertical thermal conductivity of the composite film prepared in this embodiment reached the room temperature vertical thermal conductivity (e.g., Figure 3 The strength reached 18.3 W / (m·K), and the compression rebound rate reached 94% (e.g. Figure 4 After being placed at 100℃ for 10 days, the dimensional change rate is less than 0.5% (e.g. Figure 5 ).

[0070] Example 3

[0071] This invention provides a method for preparing a polyurethane-based graphene high thermal conductivity composite film, specifically including the following steps:

[0072] (1) Weigh the raw materials according to the following weight parts: 88 parts of isocyanate-terminated polyurethane prepolymer, 5 parts of hydroxyl-modified graphene, 1.0 part of hydroxyl-modified carbon quantum dots, 0.4 parts of hydroxylated single-walled carbon nanotubes, 0.1 parts of polyacrylate dispersant, 0.3 parts of acrylic film-forming agent, and 180 parts of DMF solvent.

[0073] The preparation method of the isocyanate-terminated polyurethane prepolymer is as follows: under nitrogen protection, hexamethylene diisocyanate and polybutanediol 1000 are reacted at 75°C for 2 hours. After cooling, 1,4-butanediol, 2,2-dimethylolbutyric acid and dibutyltin dilaurate are added, and the reaction is continued at 60°C for 3 hours to obtain the isocyanate-terminated polyurethane prepolymer. The molar ratio of hexamethylene diisocyanate, polybutanediol 1000, 1,4-butanediol, 2,2-dimethylolbutyric acid and dibutyltin dilaurate is 2 mol:1 mol:0.7 mol:0.3 mol:0.02 g.

[0074] The modified graphene was prepared as follows: graphene oxide was dispersed in N,N-dimethylformamide to obtain a graphene oxide dispersion with a concentration of 50 mg / ml. Then, hexamethylene diisocyanate with a concentration of 5 mmol / L was added to the graphene oxide dispersion. The modification was completed by stirring at 80°C and 1500 rpm for 18 h under nitrogen protection to obtain the modified graphene dispersion.

[0075] The preparation method of hydroxyl-modified carbon quantum dots is as follows: using glucose as a carbon source, carbonization is carried out at 170℃ to directly prepare carbon quantum dots with hydroxyl-rich surfaces;

[0076] The preparation method of hydroxylated single-walled carbon nanotubes is as follows: single-walled carbon nanotubes are placed in a 3 mol / L sodium hydroxide aqueous solution and hydrothermally oxidized at 180℃ for 6 h to introduce hydroxyl groups into the tube wall to obtain hydroxylated single-walled carbon nanotubes.

[0077] (2) The modified graphene dispersion was added to the polyurethane prepolymer with terminal isocyanate group and reacted at 60°C for 1.5 h under the action of the catalyst dibutyltin dilaurate to achieve in-situ covalent grafting. Triethylamine was slowly added dropwise to neutralize to pH=6.5-7.5 and then the solvent was recovered by vacuum distillation to obtain polyurethane composite emulsion.

[0078] (3) Hydroxyl-modified carbon quantum dots, hydroxylated single-walled carbon nanotubes, polyacrylate dispersant (manufacturer: Wanhua Chemical; model: K45), acrylic film-forming agent (manufacturer: Shengxingxing LOCA; model: LOCA A+) and DMF solvent were added to the polyurethane composite emulsion and mixed evenly. The film was formed by doctor blade coating process with a doctor blade gap of 100 μm and dried at 90℃ for 1.5 h to obtain a polyurethane-based graphene high thermal conductivity composite film with a final film thickness of 30 μm.

[0079] Through testing, the room temperature vertical thermal conductivity of the composite film prepared in this embodiment reached the room temperature vertical thermal conductivity (e.g., Figure 3 The strength reaches 9.6 W / (m·K), and the bond strength is 2.3 MPa (e.g., Figure 7 This allows for direct bonding to the back of the chip for heat dissipation. Compared to traditional polyimide-based aluminum foil heat dissipation backsheets, the chip's operating junction temperature can be reduced by 8°C for the same thickness (e.g., ...). Figure 6 It is adapted to the ultra-thin package heat dissipation requirements of high-density integrated chips.

[0080] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polyurethane-based graphene high thermal conductivity composite film, characterized in that, The raw materials include the following parts by weight: 76-93.9 parts of polyurethane prepolymer, 5-20 parts of modified graphene, 1-3 parts of hydroxyl-modified carbon quantum dots, 0.3-0.8 parts of hydroxylated single-walled carbon nanotubes, 0.1-0.3 parts of dispersant, 0.1-1 parts of film-forming agent, and 150-300 parts of N,N-dimethylformamide.

2. The polyurethane-based graphene high thermal conductivity composite film according to claim 1, characterized in that, The modified graphene is prepared by dispersing graphene oxide in a solvent to obtain a graphene oxide dispersion, then adding an organic isocyanate to the graphene oxide dispersion, and stirring the mixture under nitrogen protection for 12-24 hours to complete the modification, thereby obtaining the modified graphene dispersion.

3. The polyurethane-based graphene high thermal conductivity composite film according to claim 2, characterized in that, The concentration of the graphene oxide dispersion is 1-100 mg / ml; The concentration of the organic isocyanate in the graphene oxide dispersion is 0.1-10 mmol / L; the organic isocyanate includes any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexylmethylene diisocyanate, phenyldimethyl diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and dimer diisocyanate. The stirring speed is 1000-2000 rpm; The reaction temperature is 70-80℃; The solvent is N,N-dimethylformamide.

4. The polyurethane-based graphene high thermal conductivity composite film according to claim 1, characterized in that, The method for preparing the hydroxyl-modified carbon quantum dots is as follows: using glucose as a carbon source, the carbon is hydrothermally carbonized to obtain carbon quantum dots with hydroxyl-rich surfaces. The method for preparing the hydroxylated single-walled carbon nanotubes is as follows: single-walled carbon nanotubes are placed in an aqueous sodium hydroxide solution for hydrothermal oxidation, and hydroxyl groups are introduced into the tube wall to obtain hydroxylated single-walled carbon nanotubes.

5. The polyurethane-based graphene high thermal conductivity composite film according to claim 1, characterized in that, The method for preparing the isocyanate-terminated polyurethane prepolymer is as follows: under nitrogen protection, organic isocyanate and polyol are reacted at 75-80℃ for 1-3 hours, and after cooling, chain extender, hydrophilic agent and catalyst are added, and the reaction is continued at 60-80℃ for 3-6 hours to obtain the isocyanate-terminated polyurethane prepolymer.

6. The polyurethane-based graphene high thermal conductivity composite film according to claim 4, characterized in that, The molar ratio of the organic isocyanate, polyol, chain extender, hydrophilic agent and catalyst is 2 mol: 1 mol: 0.7 mol: 0.3 mol: 0.02 g; The organic isocyanate includes any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexylmethylene diisocyanate, phenyldimethyl diisocyanate, 2,2,4-trimethylhexane diisocyanate, and dimer diisocyanate. The polyol includes any one of polybutylene glycol 1000, polybutylene glycol 2000, and polybutylene glycol 3000; The chain extender is 1,4-butanediol; The hydrophilic agent includes any one of 2,2-dihydroxymethylbutyric acid and 1,4-bis(2-hydroxyethoxy)benzene; The catalyst is dibutyltin dilaurate.

7. The polyurethane-based graphene high thermal conductivity composite film according to claim 1, characterized in that, The raw materials include the following parts by weight: 80-90 parts of isocyanate-terminated polyurethane prepolymer, 5-10 parts of modified graphene, 1-2 parts of carbon quantum dots, 0.5 parts of carbon nanotubes, 0.1-0.3 parts of dispersant, 0.1-1 parts of film-forming agent, and 150-300 parts of N,N-dimethylformamide.

8. The polyurethane-based graphene high thermal conductivity composite film according to claim 1, characterized in that, The dispersant is a polyacrylate dispersant; The film-forming agent is an acrylic film-forming agent.

9. A method for preparing a polyurethane-based graphene high thermal conductivity composite film according to any one of claims 1-8, characterized in that, Specifically, the following steps are included: (1) The modified graphene dispersion was added to the polyurethane prepolymer with terminal isocyanate group and reacted for 1-2 hours under the action of dibutyltin dilaurate to achieve in-situ covalent grafting. After neutralization and emulsification, the solvent was recovered by vacuum distillation to obtain polyurethane composite emulsion. (2) Carbon quantum dots, carbon nanotubes, dispersant, film-forming agent and N,N-dimethylformamide are added to the polyurethane composite emulsion and mixed evenly. The film is formed by casting or doctor blade coating process and dried to obtain a polyurethane-based graphene high thermal conductivity composite film.

10. The method for preparing a polyurethane-based graphene high thermal conductivity composite film according to claim 9, characterized in that, The specific steps of neutralization and emulsification described in step (1) are as follows: triethylamine is slowly added dropwise to neutralize to pH = 6.5-7.5; The reaction temperature described in step (1) is 60-65℃.